Genetic association study of STAT4 Polymorphisms and type 1 diabetes in Pakistani children - Rafaqat, Sana; Manzoor, Jaida; Adrees, Maria; Hamid, Hafsa; Kamal, Asifa; Bashir, Rasheeda (Penerbit Universiti Kebangsaan Malaysia, 2023)
The present study investigated the relationship of STAT4 single nucleotide polymorphisms (SNPs) rs7574685, rs10181656, and rs3821236 with T1D susceptibility visiting tertiary care hospital in Lahore, Punjab, Pakistan. One hundred and fifty-five T1D patients and one hundred and five healthy individuals were enrolled. An expert endocrinologist collected the clinical data of T1D patients. The genotyping of three potential STAT4 SNPs was performed through Tetra ARMS-PCR assay. The relationship between SNPs and T1D susceptibility under several genetic models, including dominant, recessive, and codominant models, was assessed by regression analysis. All clinical features of T1D demonstrate a significant difference from control groups (P<0.01) except blindness. The characteristic biochemical analysis determined that participants with T1D had significantly higher fasting blood glucose levels and glycated hemoglobin (HbA1c) levels than the control group (P<0.01). Genetic analysis of rs7574685 depicts GT genotype was found to be the risk allele for the development of T1D when compared to the control group. For rs10181656 and rs3821236, the GC genotype and GA genotype were observed to be the risk alleles in the T1D cases as compared to the control group (P=0.04, P<0.01, respectively). Genetic models showed that the STAT4 GG genotype of rs7574685 in the dominant model (OR=1.73, 95% CI=1.05-2.86), GC genotype of rs10181656 in the codominant model (OR=2.079, 95 % CI=1.16-3.71), and AA genotype of rs3821236 showed significant risk association with T1D (OR=3.486, 95% CI=1.72-7.03). It is concluded that the risk of T1D is highly correlated with the STAT4 variants of rs7574685 and rs10181656 among children of the Pakistani population.